Os movimentos sociais na reforma psiquiátrica/ Social movements on psychiatric reform - Amarante, Paulo; Diaz, Fernando Sobhie (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2012)
Este artigo focaliza a emergência dos movimentos sociais na reforma psiquiátrica, um fato novo na história da psiquiatria contemporânea brasileira. Trabalhou-se com o testemunho oral dos usuários de serviços de saúde mental e familiares, privilegiando-se a trajetória de militância nos movimentos sociais, captando as rupturas e instabilidades do campo psiquiátrico através das mudanças na sensibilidade coletiva. Objetiva-se se captar essas mudanças do campo, centradas no saber leigo, fora do âmbito técnico. Esta pesquisa é permeada pela seguinte interrogação: Com o surgimento dos movimentos sociais e diante das transformações evidentes no campo da assistência em saúde mental, como interpretar e analisar a ‘mentalidade manicomial’ ainda fortemente arraigada no tecido social? ABSTRACT This research focuses on the emergency of social movements linked to the psychiatric reform, which is new in the contemporary Brazilian psychiatry history. This research was elaborated on the verbal testimony of the mental health system users and their relatives, where we focused on their inclusion and participation in the social movements, thus capturing their psychiatric breakdowns and instabilities vis-a-vis the changes in the collective perception. The aim was to capture those changes on collective perception based on the point of view of the common individual, rather than employing a technical evaluation. Therefore, the main research question was: how to interpret and analyze the ‘asylum mentality’, which is strongly related to the social conscience, vis-a-vis the emergency of social movements and the changes clearly observed in the mental health assistance. KEYWORDS: History of Psychiatry; Social Movements; Psychiatry Reform.